NATURAL BASES AND ARTISTIC MEANS OF MODERN ARTS AND CRAFTS OF DAGESTAN - G. G. Gazimagomedov (Юг России: экология, развитие)
The aim is to carry out a generalized analysis of the history of formation of a new artistic language in contemporary arts and crafts of Dagestan. An innovative search for applied artist has gained further development in a series of works of the leading masters of folk arts and crafts of Dagestan. Discussion. For millennia, arts and crafts of Dagestan have been organically linked with the life of people and their everyday way of life and daily activities, with their worldview and understanding of beauty. In the middle of the 1st millennium BC in the mountainous Dagestan, art of bronze casting has reached a high degree of perfection, most vividly represented by statues of different wild and domestic animals. Images of animals are interpreted generically, without study of small details, but with the characteristic features of the exterior. Paired images of birds are often found in the arts and crafts of the medieval Dagestan. This heraldic composition, two-part or in conjunction with the sacred tree - a three-part, presented in metal-plastic and carved stone and wood, was one of the most popular and enduring decorative items that was common during the Middle Ages and has survived to the present day. This also has been further developed and improved and inherited by craftsmen of Dagestan.Conclusion. When creating works of arts and crafts craftsmen use diverse traditional arts and engineering techniques, the ancient but substantially revised and reinterpreted iconic scenes and ornamental motifs. In art, folk craftsmen emphasize the unity of man and nature. Most ornamental motifs common in Dagestan, go back to the very specific nature prototypes. Compositional structure, as the artistic analysis shows, is often borrowed from nature. This feeling becomes a condition for cultural and biological development, acting as a factor of co-evolution of man and nature.